Elucidation of hidden slow conduction by double ventricular extrastimuli: a method for further arrhythmic substrate identification in ventricular tachycardia ablation procedures. Issue 2 (24th December 2016) - Acosta, Juan; Andreu, David; Penela, Diego; Cabrera, Mario; Carlosena, Alicia; Korshunov, Viatcheslav; Vassanelli, Francesca; Borras, Roger; Martínez, Mikel; Fernández-Armenta, Juan; Linhart, Markus; Tolosana, José M; et al.
Abstract: Aims: Identification of local abnormal electrograms (EGMs) during ventricular tachycardia substrate ablation (VTSA) is challenging when they are hidden within the far-field signal. This study analyses whether the response to a double ventricular extrastimulus during substrate mapping could identify slow conducting areas that are hidden during sinus rhythm. Methods and results: Consecutive patients ( n = 37) undergoing VTSA were prospectively included. Bipolar EGMs with >3 deflections and duration <133 ms were considered as potential hidden slow conduction EGMs (HSC-EGM) if located within/surrounding the scar area. Whenever a potential HSC-EGM was identified, a double ventricular extrastimulus was delivered. If the local potential delayed, it was annotated as HSC-EGM. The incidence of HSC-EGM in core, border-zone, and normal-voltage regions was determined. Ablation was delivered at conducting channel entrances and HSC-EGMs. VT inducibility after VTSA obtained was compared with data from a historic control group. 2417 EGMs were analyzed. 575 (23.7%) qualified as potential HSC-EGM, and 198 of them were tagged as HSC-EGMs. Scars in patients with HSC-EGMs ( n = 21, 56.7%) were smaller (35.424.7 vs 67.639.1 cm 2 ; P = 0.006) and more heterogeneous (core/scar area ratio 0.250.2 vs 0.450.19; P = 0.02). 28.8% of HSC-EGMs were located in normal-voltage tissue; 81.3% were targeted for ablation. Patients undergoing VTSA incorporating HSC analysis needed less radiofrequency time (17.411 vs 2310.7 minutes; P = 0.016) and had a lower rate of VT inducibility after VTSA than the historic controls (24.3% vs 50%; P = 0.018). Conclusion: Ventricular tachycardia substrate ablation incorporating HSC analysis allowed further arrhythmic substrate identification (especially in normal-voltage areas) and reduced RF time and VT inducibility after VTSA.